The effects of cooperative learning method on the achievements and permanence of knowledge on genetics unit learned by the 8th grade students - Yıldırım, Bekir; Girgin, Sönmez (My University, 2012)
Araştırmada işbirlikli öğrenme yönteminin 8. sınıf öğrencilerinin akademik başarılarına ve bilginin kalıcılığına etkisi araştırılmıştır. Araştırmanın örneklemini, Ankara, Etimesgut’ta 8. sınıfta okuyan öğrenciler oluşturmuştur. İlköğretim 8. sınıf şubelerinden rastgele bir sınıf deney, bir sınıf kontrol grubu olarak belirlenmiştir. Deney grubunda kalıtım dersi işbirlikli öğrenme yönteminin “ayrılıp birleştirme tekniği” ile işlenmiştir. Fen bilgisi başarı testi, ön test, son test ve kalıcılık (izleme) testi olarak uygulanmıştır. Bağımlı, bağımsız gruplar için t-testi ve tek yönlü ANOVA (one way ANOVA) testi uygulanmıştır. Araştırmadan elde edilen bulgulara göre; fen ve teknoloji dersinde deney grubuna uygulanan işbirlikli öğrenme yönteminin, kontrol grubuna uygulanan öğretmen merkezli yönteme göre akademik başarı düzeyini artırmada daha etkili olduğu istatistiki olarak belirlenmiştir.

In this research, the effects of cooperative learning method on 8th grade students' academic achievements and the permanence of information were investigated. The sample involves 8th grade students in Ankara, Etimesgut. A random class of 8th grade was determined as experimental group, another class was determined as control group. In the experimental group, the genetics course was given by using the -jigsaw technique- of the cooperative teaching method. Pre-test, post-test, permanence monitoring test were applied. T-test and one way ANOVA tests were applied for dependent and independent groups. According to the data, it was detected statistically that in the science courses; the cooperative teaching method, applied to the experimental group, is more effective in increasing academic achievement than the teacher-centered method, applied to the control group.
8. Sınıf kalıtım ünitesinin öğretilmesinde işbirlikli öğrenme yönteminin öğrenci başarısına ve bilginin kalıcılığına etkisi
Keywords: Eğitim, Eğitim Araştırmaları